Pengaruh Kompetensi Kepribadian Guru Terhadap Karakter Tanggung Jawab Siswa - Rohmadi, Rohmadi; Trysha Yulindaputri (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2023)
Teacher personality competence is the ability of a teacher that is related to teacher behavior and must have good values so that they can be reflected in daily life and can carry out their duties and obligations professionally. The character of responsibility is the basic attitude of a person who is able to carry out duties and obligations and has the courage to accept all the consequences for his behavior and actions. Based on the facts in the field, it shows that there has been a decrease in the character of the responsibility of grade VII students at SMP Negeri 1 Sembawa. This type of research is a quantitative descriptive study using data collection techniques in the form of documentation, interviews, observations, and questionnaires. The analysis technique used in this research is descriptive analysis, normality test, homogeneity test, and hypothesis testing using simple regression analysis, testing the correlation coefficient and calculating the coefficient of determination. Based on the results of the study, it can be concluded that there is an effect of teacher personality competence on the responsibility character of class VII students at SMP Negeri 1 Sembawa based on the results of a simple regression analysis which obtained tcount > ttable or 14,974 > 2,042 it can be concluded that the accepted hypothesis is Ha and Ho rejected. The influence given by variable X on variable Y is equal to 88.1%, which means it has a high influence and the remaining 11.9% is influenced by other variables.